2021
DOI: 10.21608/tsnj.2021.208503
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Menopausal Symptoms among Rural Women and Their Quality of Life

Abstract: Background: Menopause is a normal physiological process of cessation of menses in women.During menopausal period women can experience many symptoms. These symptoms can be severe enough to affect their quality of life (QOL). The characteristics of rural women can affect the manifestations and treatment of their health problems. Aim of the study: to assess the relation between menopausal symptoms among rural women and their quality of life. Subjects and Method: Design: A descriptive cross-sectional study design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…On estimating the total score of menopausal symptoms intensity using the Greene Climacteric Scale (GCS), the results of the present study showed that menopausal women were more likely to have moderate intensity. The current finding is consistent with a study carried out in Tanta, Egypt, where it was reported that rural menopausal women mainly had moderate menopausal symptoms (Soliman & El-Zeftawy, 2021). This could be explained by rural women having a lower quality of life, which leads to a lower level of concern about their health.…”
Section: Discussionsupporting
confidence: 92%
“…On estimating the total score of menopausal symptoms intensity using the Greene Climacteric Scale (GCS), the results of the present study showed that menopausal women were more likely to have moderate intensity. The current finding is consistent with a study carried out in Tanta, Egypt, where it was reported that rural menopausal women mainly had moderate menopausal symptoms (Soliman & El-Zeftawy, 2021). This could be explained by rural women having a lower quality of life, which leads to a lower level of concern about their health.…”
Section: Discussionsupporting
confidence: 92%
“…Women with good nutritional status will experience menopause at a normal age while women with obesity are slower menopause. This situation is related to the amount of fat in his body which affects his reproductive hormone levels (Kupcewicz et al, 2021); (Soliman & El-Zeftawy, 2021). The results of previous studies found, the relationship between nutritional status and menopausal age, women who are overweight will experience menopause delays who are at risk for breast cancer (Meneses et al, 2020); (Shang & Xu, 2022).…”
Section: Discussionmentioning
confidence: 99%